University industry collaboration: The role of public universities within the Malaysian manufacturing landscape - Darshana, Kumari Raguphaty; Shamsuddin, Baharin; Faiz, Mohd Turan (Penerbit UMP, 2020)
In developed countries, universities are reputed as hub of innovation, contrarily to developing countries, universities are intermediary platforms for the diffusion of technology from large manufacturing companies to the value chain. The Malaysian Government through its blueprints emphasize that public universities have an important role in supporting innovation and technology commercialization. Despite myriad initiatives created and executed to help universities in improving their ability to innovate, the outcomes have yet to meet national expectations. This suggests a lack of awareness on the influence of universities especially in University Industry Collaboration (UIC) towards sustainable development in the innovation ecosystem. On that grounds, it is important to address this research gap, for it will provide insights to manufacturing companies and help universities themselves in being instrumental towards the intensification of UIC. The intent of this paper is to determine the role of public universities in UIC within the Malaysian manufacturing landscape. This paper is based on findings of a quantitative approach through survey questionnaire. A total of 20 public universities and 40 large manufacturing companies were surveyed and analysed using Descriptive statistics and Pearson’s correlation coefficient. For further evidence, registered intellectual property was analysed using One sample T-test. The percentage of expenditure of R&D per export value by large manufacturing companies in Malaysia was used as test value to determine the current role of public universities within the Malaysian manufacturing landscape. The findings reveal, public universities in Malaysia remain as intermediary platforms for large manufacturing companies to share their technology with the value chain. As intermediaries, public universities fortify knowledge and product development for large manufacturing companies. The findings further reveal, registered intellectual property by large manufacturing companies is a significant indicator of UIC outcomes through R&D processes. The findings of this paper add to the dimensions of empirical research on the significance of public universities in intensifying UIC. The importance of public universities in creating relevant and sustainable technology is paramount. Only when universities are solicited as hub of innovation by the manufacturing landscape, Malaysia will move up the value chain in manufacturing.